Long-Term Outcomes After Percutaneous Transluminal Pulmonary Angioplasty in Patients With Takayasu Arteritis and Pulmonary Hypertension - Huang, Zhiwei; Wang, Man; Hu, Fenghuan; Liu, Xiaoning (Frontiers in Immunology, 2022)
Objective: This study aimed to investigate the long-term efficacy of percutaneous transluminal pulmonary angioplasty (PTPA) for treatment in Takayasu arteritis (TA) patients with pulmonary artery stenosis and pulmonary hypertension (PH). Methods: We included 183 lesions of 79 operations in 32 TA patients with PH. Clinical symptoms, laboratory tests, World Health Organization (WHO) functional class, 6-min walk distance (6MWD), hemodynamic parameters, and prognosis were analyzed at baseline and follow-up. Results: Among the enrolled patients, comprising 28 women and 4 men. The mean age was 42.8 ± 11.9 years. The median follow-up time was 49.5 months (26-71 months). Compared with the baseline, Changes in total bilirubin, NT-proBNP, 6MWD, and WHO function class had a significant difference (all P<0.001). Echocardiography indicated that right ventricular diameter, left ventricular diameter, tricuspid annular plane systolic excursion, and estimated pulmonary artery systolic pressure were all improved (all P<0.05). Importantly, repeated right heart catheterization showed that mean pulmonary artery pressure, pulmonary vascular resistance and cardiac index were also improved significantly at follow-up (all P<0.05). Among those received stent implantation, one patient had restenosis. Unfortunately, two patients died during follow-up. One died from the aggravation of right heart failure after lung infection, the other died for traffic accident. Conclusions: This study indicated that PTPA treatment significantly improve the clinical symptoms, exercise tolerance and hemodynamic parameters in TA patients with pulmonary artery stenosis and PH. More importantly, reperfusion pulmonary edema had a significant decrease and no patient died for PTPA-related complications with the guidance of the pressure wire.